2017
DOI: 10.24269/ekuilibrium.v12i1.420
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Likuiditas, Profitabilitas, Leverage, dan Market Ratio terhadap Dividend Payout Ratio pada Perusahaan Manufaktur

Abstract: Dividend policy is concerned with financial policies regarding what amount cash dividend paid to shareholders and re-invested as retained earnings. The recent research aimed to test empirically various factors is considered to affect dividend policy. The independent variables in his research included Current Ratio (CR), Return on Equity (ROE), Debt to Equity Ratio (DER), and Earning Per Share (EPS). Meanwhile, the dependent variable was Dividend Payout Ratio (DPR). Quantitative research was used as the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
3
9
0
1
Order By: Relevance
“…Therefore, a small leverage can increase the possibility of dividend distribution because the debt that must be paid by the company is smaller. The result of this study is in accordance with the research conducted by Bramaputra et al [6] and Puspita [13] which state that leverage is a factor that causes dividend distribution. However, the result of this study contradicts the research conducted by Hardianto [14] and Nugroho and Hidayati [15] which state that leverage is not a factor that causes dividend distribution.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, a small leverage can increase the possibility of dividend distribution because the debt that must be paid by the company is smaller. The result of this study is in accordance with the research conducted by Bramaputra et al [6] and Puspita [13] which state that leverage is a factor that causes dividend distribution. However, the result of this study contradicts the research conducted by Hardianto [14] and Nugroho and Hidayati [15] which state that leverage is not a factor that causes dividend distribution.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, high or low liquidity does not affect the dividend distribution dividends. The result of this study is in accordance with the research conducted by Puspita [13] and Rokhayati et al [17] which state that liquidity is not a factor that causes dividend distribution. However, the result of this study contradicts the research conducted by Lismana [16] which states that liquidity is a factor that causes dividend distribution.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Dividend policy is closely related to companies' funding decisions because the dividend payout ratio has implications for retained earnings, one of the company's funding sources. Meaning that the greater the value of profits retained by the company, the less the amount of profit allocated to dividend payments (Puspita, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing earning per share for the most part shows the development of an organization and bringing about high market cost (Pradhan and Paudel, 2016). Earning per share is classified as a market ratio, which is one indicator to measure which stocks have the potential to benefit investors (Puspita, 2017). based on the theory above, earning per share is a ratio to measure how much profit will be obtained by investors from each share that comes from the company's revenue and it can be concluded that every income earned by the company in its operations will be distributed to investors so that it has an impact on stock prices.…”
Section: Earnings Per Sharementioning
confidence: 99%